HUBUNGAN ANTARA ADVERSITY QUOTIENT DAN MOTIVASI BERPRESTASI SISWA SEKOLAH DASAR - mildani Putri; Rahmawati Patta; Abd Kadir.A; muhammad amin (Universtas Negeri Makassar, 2022)
The problem in this study is the low ability of students in overcoming the problems faced by using their intelligence.This study aims to determine whether there is a correlation between adversity quotient and achievement motivation of fifth grade elementary school students. The population in this study were all fifth grades students of SD Gugus III Kecamatan Tanete Riattang Kabupaten Bone in the 2020/2021 academic year totaling 169 students, while the sample was 124 students using probability sampling technique, namely simple random sampling. Data analysis used inferential data analysis used Spearman Rank. Data was collected using adversity quotient and achievement motivation questionnaires. The results of this study also show that the sig-tailed < p-value (0.0001 < 0.05) at the 5% significance level. Thus, H0 is rejected and H1 is accepted. From the results of the study, it was concluded that there was a significant relationship between the adversity quotient and the achievement motivation of fifth grade elementary school students. Aspects of Adversity Quotient and students must also know the impact of the problems they face so that they are able to solve the problems they face.